The mechanism of reduction of NO with H2 in strongly oxidizing conditions (H2-SCR) on a novel Pt/MgO-CeO2 catalyst: Effects of reaction temperature - Efstathiou, Angelos M.; Costa, Costas; Savva, Petros G. (My University, 2008)
Steady State Isotopic Transient Kinetic Analysis (SSITKA) experiments using on-line Mass Spectrometry (MS) and in situ Diffuse Reflectance Infrared Fourier-Transform Spectroscopy (DRIFTS) have been performed to study essential mechanistic aspects of the Selective Catalytic Reduction of NO by H2 under strongly oxidizing conditions (H2-SCR) in the 120–300°C range over a novel 0.1 wt % Pt/MgO-CeO2 catalyst. The N-path of reaction from NO to the N2 gas product was probed by following the 14NO/H2O2 → 15NO/H2/O2 switch (SSITKA-MS and SSITKA-DRIFTS) at 1 bar total pressure. It was found that the N-pathway of reaction involves the formation of two active NO x species different in structure, one present on MgO and the other one on the CeO2 support surface. Inactive adsorbed NO x species were also found on both the MgO-CeO2 support and the Pt metal surfaces. The concentration (mol/g cat) of active NO x leading to N2 was found to change only slightly with reaction temperature in the 120–300°C range. This leads to the conclusion that other intrinsic kinetic reasons are responsible for the volcano-type conversion of NO versus the reaction temperature profile observed.
Keywords: Spectroscopy; Temperature; Catalyst supports; Chemical kinetics